Studies of the Arthropods and microorganisms of some Libyan Soils - Hammad, S.M (The Libyan Journal of Agriculture, 2023)
The populations of soil arthropods and microorganisms under six vegetable crops ( tomato. artichoke, pea, carrot, raddish and lettuce cultivated in Tripoli area, were estimated during January, 1970. All soil samples are light sandy. Tomato and artichoke soils were the richest in their total arthropod counts. Followed by carrot, pea, and finally raddish and lettuce. highest population of arthropods in artichoke and tomato soils may be attributed to their high amounts of organic fertilizers, and their well- developed growth. On the other hand, the addition of higher amounts of inorganic fertilizers in the soils of pea, carrot. raddish andlettuce, besides the evident agricultural practices in the soils of these four vegetables, may have been the cause of their lower arthropod population. The total counts Of bacteria in soils under raddish lettuce, carrot and pea were higher than hose under tomato and artichoke. Counts of spore forming bacteria, fungi and action mycetes were higher in lettuce and artichoke soils. Cellulose decomposing bacteria were higher in lettuce, tomato and raddish soils. The lower counts of total bacteria in artichoke and tomato soils may be attributed to lower amounts of soil moisture contents and lower inorganic fertilizers.